Simple capacitor dielectric sensors for determination of water content in transformer oil - Dahim, Mohammed; Al-Mattarneh, Hashem; Ismail, Rabah (International Journal of Engineering and Technology, 2018)
In this paper, two electrode dielectric sensors for evaluation of water content in transformer oil are presented. Several setup and design were investigated. Parallel plate electrode was the most optimum design. The first sensor could be used for lab testing of transformer oil while the second sensor designed to be used for online and in-situ testing. Validation and calibration standard procedures were developed for both electrode dielectric sensors. The calibration and validation standard were performed to improve the accuracy of the sensors for measuring dielectric properties of the transformer oil. The results of the dielectric constant and loss factor of transformer oil containing different amount of water content were evaluated. The results of dielectric properties also evaluated and measured in the frequency range from one kHz to one MHz. The results of complex permittivity of transformer oil show that the real and imaginary part (dielectric constant Îµ' and loss factor Îµ'') of transformer oil raise with increasing oil water content while both real and imaginary parts decline with increasing operating frequency. The dielectric sensor shows its capability to determine the water content in transformer oil and could be used for quality control of oil.Â